Cancerous Tissue Diagnosis by LIF Spectroscopy Derived From Body-Compatible Fluorophores - Asghari Moghaddam, Atefeh (J Lasers Med Sci, 2021)
Introduction: The laser-induced fluorescence (LIF) method as molecular emission spectroscopy is used to diagnose cancerous tissues. According to the previous reports, the red-shift in the fluorescence spectrum from Rhodamine 6G (Rd6G)-stained cancerous tissues compared to healthy ones impregnated with the same dye provides the feasibility for diagnosis. In this paper, we have employed the LIF emissions as a diagnostic method to distinguish between cancerous and healthy tissues infiltrated by a body-compatible fluorophore to avoid the toxicity and hazard of Rd6G dye. Methods: Biological tissue specimens are stained with sodium fluorescein (NaFl) dye and then irradiated by the blue CW diode laser (405 nm) to examine the spectral properties that are effective in detecting cancerous tissues. Results: The spectral shift and the intensity difference of fluorescence are keys to diagnosing in vitro cancerous breast, colon, and thyroid tissues for clinical applications. The notable tubular densities in the breast and colon tissues and the space between the papillae in the thyroid ones cause the cancerous tissues to be prominently heterogeneous, providing numerous micro-cavities and thus more room for dye molecules. Conclusion: Here, we have assessed the spectral shift and intensity difference of fluorescence as a diagnostic method to distinguish between cancerous and healthy tissues for clinical applications.